Chinese Economy in 2050 - The Key Challenges on the way to Grow - Rubaj, Piotr (Journal of Reviews on Global Economics, 2017)
China attracts people with its geographic and economic diversity, an impressive heritage of over three thousand years old civilisation and the size of population which creates different opportunities for business. Understanding past and current reality of this country seems to be difficult as its economic and political system is somewhere in between bureaucratic and authoritarian one-party state and market orientated modern economy. The State centre within last three decades became one of the most important players in the world on political, economic and military scenes. It has the largest population, the most numerous army, nuclear weapons, large surplus in foreign trade balance, central bank reserves amounting 3,5 trillion USD and its national currency named yuan, which already has become a part of SDR. Nowadays China is on the way to become the world largest economy with independent impact on global political and economic affairs. This country is also facing a list of problems, which seem to be very serious and which will be challenging authorities and society in coming years and decades. One of the most important is necessity to strength environmental regulations to improve quality of life and to decrease the level of destruction of nature, secondly to support human capital to facilitate transition to higher value-added economy, it means to increase internal consumption and the third to boost rural development, which is slow, ineffective and it creates significant differences in individual incomes between urban and country regions. The speed of economic growth seems to be essential for business, stock exchanges and foreign investors and therefore questions concerning the barriers on the road to grow seem to be essential for coming years. This article is a trial to indicate these key challenges and threats for China on the way to grow.